Thrive : how schools will win the education revolution - Lichtman, Grant, 1956- (Corwin, 2020)
"We need great schools that provide great learning to not only survive, but thrive. There is great news. We know how to deal with these evolutionary pressures. We know how to not only survive, but thrive when competition forces or allows us to change. This book translates that knowledge into the language of how schools actually work and how educators actually approach their critical jobs"--